(untitled) (Herald of Journalism, 2024)
In journalism there is the concept of transmedia. In general, transmedia deals with the presentation of information in various media. Unlike multimedia, all media are interconnected. For example, only transmedia technology can allow the plot of a novel to be adapted into a film with minor changes, or the first part of a story to be told through a television show, the second part through a film, and the third part through a television show. In the world at large, there are different ways of disseminating the essential elements of fiction. Transmedia information is an output system. The information it contains is mostly related to history. The narrative structure will be filled with historical data and will include text and audio, video, fonts, images, infographics and more. Each text can create a story itself. Each element contributes to the main story. This is why the effectiveness of transmedia is directly related to the method of storytelling. The purpose and main direction of the scientific article was to study the features of the process of formation of new multimedia genres in online media, to focus on the features of methods of transformation and presentation of existing genres in other forms. The scientific and practical significance of the article lies in the attempt to monitor new terminology genres in the Kazakh-language media, such as longread, construction, short video recording with the mention of new trends in Kazakh journalism. In the course of the study the method of comparative analysis was used. The main result of the analysis was the consideration of characteristics and trends in the dynamics. By analyzing materials published on the sites, such as Malim.kz, Massaget.kz, Balbal.kz, we tried to reveal the nature of the new trend in genres such as storytelling, longread, which meet modern demand. The relevance of the scientific research is determined by the consideration of competitiveness criteria and trends in new formats for presenting general media journalistic materials.